Advocacy of violence against women through the implementation of cyber public relations at the Rifka Annisa women's Crisis Center - Amanova, Felicciana Yayi Amanova; Andryani, Kristina Andryani (COMMICAST, 2023)
This research examines the implementation of Cyber Public Relations at the Rifka Annisa Women's Crisis Center (Rifka Annisa WCC) in advocating public awareness of violence against women. This study aims to identify the obstacles Rifka Annisa WCC faces in managing Cyber Public Relations activities, analyze how they address those obstacles, and examine the impact of Cyber Public Relations implementation on advocacy of violence against women.. This research employs a qualitative case study method through observation and in-depth interviews with Rifka Annisa WCC's media officer. The study objectives are presented using the concepts of Cyber Public Relations and Social Media. The study results found that the lack of human resources in managing social media hindered Rifka Annisa WCC in optimizing Cyber Public Relations activities to advocates public awareness. To address this obstacle, Rifka Annisa WCC focuses on using Instagram as an online advocacy tool. Furthermore, the application of Cyber Public Relations in Rifka Annisa WCC's advocacy activities had a significant impact on aspects of community literacy regarding the discourse on violence against women, as well as changes in the behavior of victims of violence and the larger community in responding to violence against women.